PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP IMPLEMENTASI KEBIJAKAN PERPUSTAKAAN DESA DI KPADD KABUPATEN KAYONG UTARA - Saraswati E.42008067, Ika Meiria Dian (FISIP Universitas Tanjungpura Pontianak, 2012)
This research aims to identify and analyze the effect of competence of Human Resources (HR) on villagelibrary policy implementation at the Kantor Perpustakaan, Arsip dan Dokumentasi Daerah (KPADD) ofNorth Kayong Regency. Data collected through distributing questionnaires to 11 people managing thevillage library were analyzed with the help of Product Moment Correlation Formula, Coefficient ofDetermination Formula and Simple Linear Regression Formula in SPSS 18. The results showed that thecompetence analysts Human Resources has a positive influence on the village library policyimplementation or equal to 0.585 (58.5%) and 41.5% determined by other variables. In addition, theregression equation between variables competencies of Human Resources at the village libraryimplementation of the policy variable is Y = 0.811 + 0.738 X. The regression equation shows that theregression coefficient between variables x and y variables is 0.738. This coefficient means that anyincrease in one variable value human resource competencies (X) can influence on policy implementationincreased by 0.738 times the village library.Key Words: Competence, Human Resources, Policy Implementation, Village Library